The Influence of Federal Funds Rate Volatility Before and During The Covid-19 Pandemic on Economic Stability in Asean Countries - Sidha Belanandra Radise; Etty Soesilowati; Agung Haryono (PT. Maju Malaqbi Makkarana, 2023)
The purpose of this study is to analyze the effect of the Federal Funds Rate before and during the Covid-19 pandemic on economic stability in five developing countries in the Southeast Asian region which are members of an economic and geopolitical organization, namely the Association of Southeast Nations (ASEAN) to see short-term relationships. and long-term during that period. The indicators of economic stability used are the benchmark interest rate for deposits, the reference interest rate for loans, the balance of payments which includes exports and imports, inflation, exchange rates, and the money supply. In this study, the method used was the quantitative method and the data obtained was secondary data sourced from International Financial Statistics (IFS) from January 2015 to December 2022 which used the Vector Error Correction Model (VECM) approach in the Eviews 9 application. The results found indicated that in the long run, the existence of FFR volatility has a positive effect on the Deposit and Export Reference Rates. While those that have a negative effect are Loan Reference Rates, Imports, Exchange Rate Inflation, and Money Supply. In the short term, the existence of the FFR interest rate has a positive effect on the Reference Rates for Deposits, Imports, and Inflation. While those that have a negative effect are Loan Reference Rates, Exports, Exchange Rates, and Money Supply